Contribuição ao processo de afiação de ferramentas monocortantes de aço rápido - De Paiva, Raphael Lima; Da Silva, Rosemar Batista; Arencibia, Rosenda Valdés; Ruzzi, Rodrigo De Souza [UNESP]; Bianchi, Eduardo Carlos [UNESP]; de Aguiar, Paulo Roberto [UNESP] (FapUNIFESP (SciELO), 2017)
Despite of technological advances in developments of cutting tools such as carbide inserts, ceramic materials and others in the last three decades, some of cutting tools still needs to have their cutting geometry restored due to wear through the sharpening operation with abrasive wheels. Sharpening aims to provide shape either to new cutting tools and worn ones. The efficiency of this operation depends on the correct selection of cutting parameters, machine tool and operator’s ability. In this process, if an improper cutting parameter is selected, the workpiece geometry can be compromised and, at the worst-case scenario, surface burning can occur, thereby leading to reduction of tool hardness. Tool hardness and strength are essential to withstand cutting forces during machining, for example, when a lathe tool bit is employed for cylindrical turning of a mild steel. In this context, this work presents an experimental study on the sharpening operation of HSS lathe tool bit using four different values of depth of cut. The grinding wheel employed was a straight cup white aluminium oxide, which is highly recommended for such operation. The workpiece material was the high speed steel (HSS) with hardness of 62 ± 2 HRC. The output parameters evaluated were the values of the rake angle, side cutting edge angle and end cutting edge angle, that were all measured with aid of a profile projector and a universal protractor (only for the rake angle). All the experimental trials were replicated once and the angles were measured five times. Statistical analyses of the results were performed to evaluate the statistical significance of comparisons and the measurement uncertainty was calculated. The results showed that all the angles were affected by the depth of cut, as expected, and the highest angles accuracy was obtained after machining with a depth of cut of 0.06 mm. No burrs and burning of the machined surfaces were observed.
Contribution to sharpening operation of HSS lathe tool bit
Keywords: Angles; Depth of cut; Machining; Measurement uncertainty; Sharpening cutting tools